Effect of Different Rates and Time of Application of Phosphorus on Yield, Soil Fertility, Nutrient Uptake and Monetary Returns of No-till Maize (Zea mays L.) after Lowland Rice - Ramesh, Ch.; Ramana, M. Venkata; Sree, G. Jaya (International Journal of Economic Plants, 2022)
Field experiment was conducted during dry seasons for 2 consecutive years at College of Agriculture, Rajendranagar, Hyderabad on no-till maize after lowland kharif rice on sandy clay loam soil. The experiment was laid out in randomized block design with factorial concept and replicated thrice. Treatments executed are three Phosphorus levels (30, 45 and 60 kg P2O5 ha-1) and three Phosphorus application times (at 10 days before harvest of rice, at the time of sowing of maize and at the time of first irrigation to maize). The results revealed that application of 60 kg P2O5 ha-1 recorded superior grain and stover yield, gross returns, net returns, benefit cost ratio and nutrient uptake (Nitrogen, Phosphorus and Potassium) at crop harvest over that of 45 and 30 kg P2O5 ha-1. But, application of 60 kg P2O5 ha-1 left behind the soil with lower amount of available Nitrogen and Potassium and higher Phosphorus status after harvest of the crop. Application of phosphorus at 10 days before harvest of rice and at the time of sowing of maize being on par resulted in better grain and stover yield of maize, gross returns, net returns, benefit cost ratio and nutrient uptake (Nitrogen, Phosphorus and Potassium) at crop harvest over its delayed application (at the time of first irrigation to maize). The application of Phosphorus at 10 days before harvest of rice or at the time of sowing of maize depleted greater amount of available Phosphorus from the soil than its application along with first irrigation.